Transcatheter and surgical treatment of tricuspid regurgitation: Predicting right ventricular decompensation and favorable responders - Sala, Alessandra; Beneduce, Alessandro; Maisano, Francesco (Frontiers in Cardiovascular Medicine, 2022)
Isolated tricuspid regurgitation (TR) has gained increasing recognition in recent years both in the surgical and in the cardiological community. Left untreated, isolated TR significantly worsens survival. Despite being a strong predictor of negative prognosis, interventions to correct TR are rarely performed due to increased surgical risk and late patient presentation. Recently, the ultimate focus has been on patient selection, surgical or transcatheter indication, and correct timing. Furthermore, of paramount importance is the identification of predictors of outcome following treatment, in order to discriminate between favorable and unfavorable responders and guide the decision-making process of the most adequate treatment for every patient.